2011
DOI: 10.1137/080731311
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Symbol Calculus

Abstract: This paper deals with efficient numerical representation and manipulation of differential and integral operators as symbols in phase-space, i.e., functions of space x and frequency ξ. The symbol smoothness conditions obeyed by many operators in connection to smooth linear partial differential equations allow to write fast-converging, non-asymptotic expansions in adequate systems of rational Chebyshev functions or hierarchical splines. The classical results of closedness of such symbol classes under multiplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Discrete symbol calculus (DSC) is a natural answer to this question [13]. With the help of DSC, constructing P and P −1 takes only a number of steps that is polylogarithmic in N .…”
Section: Factorizing This Operator Equation Givesmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrete symbol calculus (DSC) is a natural answer to this question [13]. With the help of DSC, constructing P and P −1 takes only a number of steps that is polylogarithmic in N .…”
Section: Factorizing This Operator Equation Givesmentioning
confidence: 99%
“…Concerning fast computation of general pseudodifferential and Fourier integral operators (FIO), Candès and the authors have reported on different ideas in [13,7,8]. Many of the algorithmic tools used in those papers are present in different forms or different contexts; let us for instance mention work on angular decompositions of the symbol of pseudodifferential operators [1], work on the butterfly algorithm and its applications in [21,23,38,37,35], work on fast "beamforming" methods for filtered backprojection for Radon and generalized Radon transforms (a problem similar to wave propagation) in [36,22,2], work on the plane-wave time-domain fast multipole method summarized in Chapters 18 and 19 of [9], and work on "phase-screen" methods in geophysics [11].…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of algorithm can be quite efficient if fast algorithms for calculating Gv are available (without the explicit knowledge of G). Examples of such fast algorithms include multigrid methods [6], the fast multipole method [13] (combined with iterative solvers), and the discrete symbol calculus [9], to name a few. One shortcoming of this approach is that the accuracy is relatively low for general G due to its Monte Carlo nature.…”
Section: Related Workmentioning
confidence: 99%
“…Because it s a function of both space and wave-vector, we can refer to H as a dip-dependent and scale-dependent scaling. Under this pseudodifferential model, it is possible to define B i from elementary symbols, by adapting the "discrete symbol calculus" approach of (Demanet and Ying (2011)). In other words, each B i is a pseudodifferential operator with a symbol that uses a single basis function such as Fourier sine or cosine.…”
Section: Matrix Probingmentioning
confidence: 99%